In search of philosophic understanding - Burtt, Edwin A. (A Mentor Book, 1967)
Historical survey of Western philosophy; The philosophical role of " presupposition"; common sense knowledge and its revision; The ways of intuitionism, rationalism, and empiricism; What is fact? Varying criteria of fact, of form, and of value; Linguistic analysis as the task of philosophy,....